Biosphere Reserve as Learning Sites for Biocultural Conservation Education; Case of Mount Hakusan Biosphere Reserve in Japan - Mammadova, Aida (European Journal of Sustainable Development, 2017)
Biosphere Reserves (BRs) are highly recognized areas under UNESCO’s MAB Programme for their conservation, learning and sustainable development initiatives. Even though Mount Hakusan BR (MHBR) in Japan was designated in 1980, its transition zone was recognized in 2016, and area still lacks any implementations or functions as BR. We suggested that introducing the place-based learning will be one of the most important logistic functions of MHBR, and it will provide the site- specific knowledge and experience for bio-cultural education. We conducted five educational fieldworks at MHBR sites, with the objectives to assess the site-specific elements that links biological and cultural diversity of the region. Each field provided thematic understanding of ecosystems of the MHBR, such as forest, hydrology, wildlife, culture, livelihood as well as conservation initiative and tourism. Participant were 21 academic students. As the outcome of the course, several natural and cultural resources were assessed by the students as valuable “treasures” of the region. However, we found that local residences were not aware about the values of those regional resources, and about the role of MHBR as designated area. In future, we plan to evaluate the awareness change of local people before and after implementation of the educational fieldworks together with the youth, at BR sites.